2019
DOI: 10.5194/acp-19-3779-2019
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality in the Δ<sup>33</sup>S measured in urban aerosols highlights an additional oxidation pathway for atmospheric SO<sub>2</sub>

Abstract: Abstract. Sulfates present in urban aerosols collected worldwide usually exhibit significant non-zero Δ33S signatures (from −0.6 ‰ to 0.5 ‰) whose origin still remains unclear. To better address this issue, we recorded the seasonal variations of the multiple sulfur isotope compositions of PM10 aerosols collected over the year 2013 at five stations within the Montreal Island (Canada), each characterized by distinct types and levels of pollution. The δ34S-values (n= 155) vary from 2.0 ‰ to 11.3 ‰ (±0.2 ‰, 2σ), t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
4

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 133 publications
(213 reference statements)
2
53
4
Order By: Relevance
“…More locally, a recent study reported a I. Genot et al: Oxygen and sulfur mass-independent isotopic signatures narrow range from −0.57 ‰ to 11.33 ‰ for sulfur emitted by transport and industries in Paris (Au Yang et al, 2020). Lee et al (2002) carried out vegetation and diesel combustion experiments, resulting in δ 34 S and δ 18 O values between 9.55 ‰ and 16.42 ‰ and between 5.5 and 10.5 ‰, respectively, with O of ∼ 0 ‰, forming primary sulfates without mass-independent signatures.…”
Section: Source Effectsmentioning
confidence: 99%
“…More locally, a recent study reported a I. Genot et al: Oxygen and sulfur mass-independent isotopic signatures narrow range from −0.57 ‰ to 11.33 ‰ for sulfur emitted by transport and industries in Paris (Au Yang et al, 2020). Lee et al (2002) carried out vegetation and diesel combustion experiments, resulting in δ 34 S and δ 18 O values between 9.55 ‰ and 16.42 ‰ and between 5.5 and 10.5 ‰, respectively, with O of ∼ 0 ‰, forming primary sulfates without mass-independent signatures.…”
Section: Source Effectsmentioning
confidence: 99%
“…Although most of the TC mass is concentrated in the finest PM fractions (up to 90%; Sudheer et al, 2016), our results showed that the carbonaceous fractions studied here were significantly contributing in our TSP aerosols samples (from 5 to 26%). For all carbon fractions, there was a tendency to observe the lowest concentrations at station 99 (Kruskal-Wallis ANOVA test at 0.05 level, Table 1), located at the western end of the island, that is representing the local background (e.g., Au Yang et al, 2019). The rest of the stations showed similar results for all carbon fractions, suggesting a homogeneous influence of carbonaceous aerosols for most of the urban and industrial parts of island covered by these stations.…”
Section: Characteristics Of the Carbon Fractionsmentioning
confidence: 99%
“…Four monitoring stations (number 03, 06, 13, and 99; Figure 1) were selected as they represent the major environmental conditions encountered on the island in terms of atmospheric contamination (Au Yang et al, 2019): (i) station 03 ("Saint-Jean-Baptiste") is located at the north-eastern end of the island and is typically influenced by local petro-chemical industries, (ii) station 06 ("Anjou") is located close to the intersection of two of the main high-traffic highways (highways 40 and 25) on the island, (iii) station 13 ("Drummond") is located downtown and represents the urban background, whereas iv) station 99 ("Sainte-Anne-de-Bellevue") is located at the western end of the island in a semi-rural environment about 35 km WSW of Montreal downtown and is more likely to sample regional aerosols generated upstream the city and transported to Montreal (Au Yang et al, 2019).…”
Section: Samples and Sampling Sitesmentioning
confidence: 99%
“… Mass independent sulfur isotope effects observed in coal, tropospheric aerosols and SO 2 in the modern atmosphere. Data compilation is obtained from Lin et al., Shaheen et al., and Au Yang et al …”
Section: Present‐day Sulfur Isotopic Anomaliesmentioning
confidence: 99%
“…The major challenge to explain the observed sulfur isotopic anomalies in combustion‐related primary sulfates is that a proper and quantitative description of the isotopic partitioning and exit channels such as gas‐to‐solid formation processes is required. A most recent study measured positive Δ 36 S values in some aerosol samples collected from Canada, in contrast to the early combustion chamber experiment and most ambient sulfate aerosols display negative Δ 36 S values (Figure ). On a view of isotopic mass balance, this result is not surprising, though a quantitative explanation remains lacking.…”
Section: Underappreciated Mass Independent Sulfur Isotope Effectsmentioning
confidence: 99%